Quantitative assessment of barriers to the clinical development and adoption of cellular therapies: A pilot study. - Davies, B; Rikabi, S; French, A; Pinedo-Villanueva, R; Morrey, M; Wartolowska, K; Judge, A; Maclaren, R; Mathur, A; Williams, D; Wall, I; Birchall, M; et al. (2014)
There has been a large increase in basic science activity in cell therapy and a growing portfolio of cell therapy trials. However, the number of industry products available for widespread clinical use does not match this magnitude of activity. We hypothesize that the paucity of engagement with the clinical community is a key contributor to the lack of commercially successful cell therapy products. To investigate this, we launched a pilot study to survey clinicians from five specialities and to determine what they believe to be the most significant barriers to cellular therapy clinical development and adoption. Our study shows that the main concerns among this group are cost-effectiveness, efficacy, reimbursement, and regulation. Addressing these concerns can best be achieved by ensuring that future clinical trials are conducted to adequately answer the questions of both regulators and the broader clinical community.